(untitled) (Journal of Management & Business, 2025)
This study examines the relationship between social network behavior and the development of leadership capacities among university students, using Social Network Analysis (SNA) as the primary methodological tool. A total of 156 questionnaires were administered to 13 fourth-year students in the Business Administration and Enterprise Development program, measuring 10 leadership dimensions (based on the Bass and Avolio model) through 12 instruments. A contextualized learning approach was adopted (leader/group/context). Pajek and Gephi software were used for descriptive network analysis, identifying leadership styles (Transformational, Transactional, and Laissez-faire) both independently and simultaneously. Pearson correlations were calculated, and the QAP test was applied for statistical analysis. Key findings indicate that leadership within social networks is dynamic and influenced by interactions. Effective leadership styles (e.g., Transformational) can shape network structures. A high correlation was found between idealized influence (attributed and observed) and a notable relationship between intellectual stimulation and inspirational motivation. This study contributes to the understanding of transformational leadership in higher education, particularly in classroom settings, and offers insights for the development of university leaders in a globalized economy.